The Critical Aspect on Fair Value Accounting and its Implication to Islamic Financial Institutions - Safri Haliding (Global Review of Islamic Economics and Business, 2014)
Recently, fair value measurement and its implication in accounting standards have been increasing (Ramanna, 2006). One of the important aspects of financial reporting is measurement (Barth, 2007). Barlev and Haddad (2003) state that the fair value accounting(FVA) paradigm replaced the historical cost accounting (HCA) in the development of accounting standards that FVA is more value relevant that HCA probably did not provide the real financial information and income. However, previously studies mention that fair value accounting suffers from some serious limitations and disadvantages such as issues in market approach, income approach, and cost approach. Al-Yassen and Al-Khadash (2011) argue that accounting standard setters such as the International Accounting Standards Board (IASB) UK and the Financial Accounting Standards Board (FASB) U.S as well as other national accountingstandard setters provide high attention and long-term ambition to use fair value accounting as full measurement in all financial instruments. Islamic Financial Institutions (IFIs) that have different objectives and principles as well as have different financial products with conventional financial institution. This paper tries to explore critical aspects of the fair value accounting andits implications to Islamic Financial Institutions implications. This study concludes that that fair value accounting measurement provides many critical aspects to be implemented to Islamic Financial Institutions (IFIs). Additionally, AAOIFI proposed cash equivalent value as respond to fair value measurement that cash equivalent value when the attribute condition are present such as the relevance, reliability and understandability of the resulting information. Furthermore, fully adopting International Financial Reporting Standards (IFRS) issued by IFRSIASB, there will no specific standards for unique functions of Islamic Financial Institutions. Inaddition, the paper may be recommended to work together among Muslim countries to unity the potential harmonizing one set accounting standards for Islamic Financial Institutions such as AAOIFI?s standards.